MANAJEMEN USAHA DAN KEWIRAUSAHAAN DENGAN MEMANFAATKAN SUMBER DAYA LAUT DI KAMPUNG ENGGROS - Westim Ratang; Hesty T. Salle; Paulus K. Allo Layuk; Klara Wonar; Gabriel Yusuf; Yohanis Rante (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Enggros Village in Jayapura City, Papua, has abundant marine resources, but their utilisation remains traditional, resulting in suboptimal economic value. This community service activity was carried out on 1 May 2025, involving 22 women from the Betlehem Enggros Protestant Church congregation. The aim of the activity was to improve fish processing skills to make fish nuggets and to provide entrepreneurial skills to open up small business opportunities. The training was conducted in two sessions, namely practical fish nugget making and entrepreneurship learning. The evaluation results showed a significant increase in the participants' knowledge and skills. Participants who initially did not understand the processing process were able to explain the steps of production, produce ready-to-eat nuggets, and understand simple marketing strategies, pricing, and household financial management after the training. The visible social impact was a growth in confidence, motivation to become entrepreneurs, and the emergence of initiatives to form congregational business groups. This activity has made a tangible contribution to community empowerment, promoting economic independence, and strengthening community-based social solidarity.